1997
DOI: 10.1002/(sici)1097-4644(19970315)64:4<595::aid-jcb8>3.0.co;2-m
|View full text |Cite
|
Sign up to set email alerts
|

Binding, internalization, and degradation of antiproliferative heparan sulfate by human embryonic lung fibroblasts

Abstract: Binding, internalization, and degradation of 125I-labeled, antiproliferative, or nonantiproliferative heparan sulfate by human embryonic lung fibroblasts was investigated. Both L-iduronate-rich, antiproliferative heparan sulfate species as well as L-iduronate-poor, inactive ones were bound to trypsin-releasable, cell-surface sites. Both heparan sulfate types were bound with approximately the same affinity to one high-affinity site (Kd approximately 10(-8) M) and to one low-affinity site (Kd approximately 10(-6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0
1

Year Published

2000
2000
2005
2005

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 39 publications
(36 reference statements)
3
16
0
1
Order By: Relevance
“…HS6 binds to one high affinity site and to one low affinity site on the cell surface of fibroblasts [14]. As shown previously DexS, is without significant effect on cell proliferation [13] and MAP kinase activation (Fig.…”
Section: High Affinity Site Of Binding Of Heparan Sulfate (Hs6) May Bsupporting
confidence: 71%
See 3 more Smart Citations
“…HS6 binds to one high affinity site and to one low affinity site on the cell surface of fibroblasts [14]. As shown previously DexS, is without significant effect on cell proliferation [13] and MAP kinase activation (Fig.…”
Section: High Affinity Site Of Binding Of Heparan Sulfate (Hs6) May Bsupporting
confidence: 71%
“…HS2, CS nor DexS, which do not inhibit cell proliferation or antiproliferative DS had any significant effect on ERK activation, whereas antiproliferative HS (HS6) and heparin had strong anti-ERK effects. Arroyo-Yanguas et al [14] showed previously that antiproliferative DS do not bind very well to the cell surface, whereas HS does, suggesting that the inhibitory effects of MAP kinase are mediated through interactions on the cell surface. Both HS6 and heparin have high contents of both sulfation and IdoA, whereas HS2, with lower amounts of sulfation and IdoA was unable to affect MAP kinase activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The final preparation step was separation on a Sepharose 6 column under dissociative conditions to remove cytoactive components bound to the HS. The procedure for the determination of total hexosamine, IdoUA, and sulfate content has earlier been described (18)(19)(20). Chemical data for the HS2 and HS6 used in the study are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%